Theodor and Marcella Boveri : chromosomes and cytoplasm in heredity and development - Satzinger, Helga (My University, 2008)
The chromosome theory of heredity, developed in 1902–1904, became one of the foundation stones of twentieth-century genetics. It is usually referred to as the Sutton-Boveri theory after Walter Sutton and Theodor Boveri. However, the contributions of Theodor Boveri and his co-worker, Marcella O’Grady Boveri (also his wife), to the understanding of heredity and development go beyond the localization of the Mendelian hereditary factors onto the chromosomes. They investigated the interaction of cytoplasm and chromosomes, and demonstrated its relevance in heredity and development.
Keywords: Entwicklung; Geschichte; Genetik; 570 Biowissenschaften; Biologie